Projeto de conversores estáticos fazendo uso de uma metodologia de minimização de volume/perdas/custo - Sartori, Hamiltom Confortin (2013)
This thesis presents a new optimization design methodology for power electronics converters with volume, cost and efficiency objectives. The optimization methodology, achieved by mathematical interactions, is based on the concept of the converter integrated design. In other words, the main physical converter components are designed simultaneously in the function of a common variable. The integrated design provides for the reduction of cost and time of the system design and also gives complete and matched solutions with the objective of the proposed optimization. The proposed methodology is illustrated with the help of a case study of a Boost Power Factor Correction converter (PFC) including an input EMI filter. In this case study, three different magnetic materials are used in both inductors designs (Boost and EMI filter), different semiconductors technologies and heat sink profile are also analyzed, aiming to demonstrate how technology affects the volume, cost and efficiency of the converter. Furthermore, switching auxiliary circuits (snubber and ZVT) are designed and its volume, cost and efficiency results are compared to the converter with hard switching. To confirm the models and theoretical analysis that was carried out, the experimental mechanical, electrical and thermal measurements are presented.